1999
DOI: 10.1002/(sici)1099-1387(199904)5:4<185::aid-psc184>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Structural requirements for cellular uptake of α-helical amphipathic peptides

Abstract: The structure of the cell-permeable alpha-helical amphipathic model peptide FLUOS-KLALKLALKALKAALKLA-NH2 (I) was modified stepwise with respect to its helix parameters hydrophobicity, hydrophobic moment and hydrophilic face as well as molecular size and charge. Cellular uptake and membrane destabilizing activity of the resulting peptides were studied using aortic endothelial cells and HPLC combined with CLSM. With the exceptions that a reduction of molecule size below 16 amino acid residues and the introductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
107
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 147 publications
(121 citation statements)
references
References 30 publications
(29 reference statements)
12
107
1
Order By: Relevance
“…The mechanism of PTD-mediated protein transduction, independent of energy and receptors binding, has not yet been fully elucidated. A nonspecific electrostatic interaction of basic amino acids PTD with cellular membrane might be the first crucial step (Bellet-Amalric et al, 2000); heparan sulfate in the cytoplasm (Rusnati et al, 1999;Ziegler and Seelig, 2004) and amphiphilic a-helices of PTD might be required during the transduction (Scheller et al, 1999). For the hippocampal slices, we obtained a similar result; after incubation with FITC-labeled PTD-CaBD, most of the cells showed FITC-positive staining.…”
Section: Discussionsupporting
confidence: 76%
“…The mechanism of PTD-mediated protein transduction, independent of energy and receptors binding, has not yet been fully elucidated. A nonspecific electrostatic interaction of basic amino acids PTD with cellular membrane might be the first crucial step (Bellet-Amalric et al, 2000); heparan sulfate in the cytoplasm (Rusnati et al, 1999;Ziegler and Seelig, 2004) and amphiphilic a-helices of PTD might be required during the transduction (Scheller et al, 1999). For the hippocampal slices, we obtained a similar result; after incubation with FITC-labeled PTD-CaBD, most of the cells showed FITC-positive staining.…”
Section: Discussionsupporting
confidence: 76%
“…Nevertheless, the lack of six C-terminal amino acids completely prevents any actin binding (Turunen et al, 1994). To investigate the role of moesin in regulating the actin cytoskeleton in CD8 cells, a peptide corresponding to a highly conserved sequence in the ERM family at the C-terminal domain (ERM peptide) was synthesized and introduced into CD8 cells as described by Oehlke (Oehlke et al, 1998;Scheller et al, 1999) (Fig. 2A).…”
Section: Resultsmentioning
confidence: 99%
“…A number of other cell-penetrating peptides that derive not from natural proteins but from the engineering of various short peptides have been described, such as, for example, transportan, 10,20 the model amphipathic peptide (MAP), 16,17 and various signal sequence-based peptides, 11,12 and homoarginine vectors 34 (see Tables 1 and 2). Transportan is a 27-amino-acid chimeric peptide composed of the neuropeptide galanin and mastoparan-X linked by a central lysine.…”
Section: Other Cell-penetrating Peptidesmentioning
confidence: 99%
“…10 Likewise, it has been reported that MAP and some of the other sequence-based peptides seemingly enter into cells via a nonendocytotic pathway. 11,12,16 The sequence-based peptides resulted from the fusion of a hydrophobic peptide (eg, a signal sequence, a fusion peptide) with the NLS motif, whereas the MAP peptide is a complete canonical amphipathic helix. As observed with pAntp [43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58] , the unconventional internalization of these peptides seems to be neither saturable nor dependent on the cell type 8,10 and could be related to their lipid-binding capacity.…”
Section: Other Cell-penetrating Peptidesmentioning
confidence: 99%